A new upper bathyal species of Protankyra (Holothuroidea: Apodida: Synaptidae) from the tropical southwest Atlantic - Moura, Rafael Bendayan De; Lavrado, Helena Passeri; Campos, Lúcia S. (Zootaxa, 2026)
One of the main objectives of the “Program for the Assessment of the Sustainable Potential of Living Resources in the Brazilian Exclusive Economic Zone” (REVIZEE) was to produce a comprehensive inventory of benthic communities off the Brazilian coast. Holothuroid specimens collected at a depth of 246 m off the Rio de Janeiro state were donated for this study. Protankyra estevesi sp. nov. is described and illustrated herein based on morphological characters from a complete specimen and seven posterior fragments. The ossicles were examined using both optical and scanning electron microscopy. Micro-CT imaging was used to explore the calcareous ring elements in detail. The new species has eight long Polian vesicles. The main body wall ossicles consist of anchors and anchor plates, which are smaller anteriorly than posteriorly. Two types of anchor plates are found varying in size and shape. Posterior anchors are 1000 µm in size, and their arm serrations (up to 31) are occasionally discontinuous. Additional body wall ossicles include abundant C-shaped, round, and elongated miliary granules. The calcareous ring is composed of alternating five interradial and five radial pieces; dorsal pieces are shorter than ventral ones. In contrast, RIV and RV are wider than the other radials, each bearing two anterior processes, and the perforation is located in the muscle process. The new species was compared with 37 other congeners distributed worldwide. This is the first report of a deep-sea synaptid species in the southwestern Atlantic off Brazil. There is high potential for marine biodiversity investigations in the region and new species can be revealed not only in newly sampled deep-sea environments but also from studies based on material deposited in zoological collections.